Primary Adrenal Insufficiency due to Tuberculosis Infection Pitfalls in Diagnosis and Management - Ira Laurentika; Em Yunir; Tri Juli Edi Tarigan; Agnes Stephanie; Robert Shinto; Taufik Agung (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2024)
Primary adrenal insufficiency (PAI) is a chronic condition in which both adrenal glands are not able to produce steroid hormones. In this article we reported a-20-year-old male with history of soft tissue tumor in thoracalregion and general hyperpigmentation of skin and mucous. Laboratory findings showed hypocortisolism and adrenal computed tomography (CT) scan showed bilateral enlargement of adrenal with multiple necrotic nodular lesion and calcification, suggesting adrenal metastasis or tuberculosis infection. The interferon gamma release assay (IGRA) and histopathology review of the specimen from soft tissue tumor in thoracal region showed confirmed the diagnosis of adrenal tuberculosis. Antituberculosis drugs were started, and hydrocortisone dose were frequently adjusted. Five months after therapy the patient is clinically improved with a minimal dose of steroid.